The Influence of Spiritual Leadership, Organizational Climate and Toxic Workplace on Employee Performance in the South of Bengkulu District Health Office - Syaifullah, Syahrul; Suryosukmono, Gerry; Sugeng Susetyo (Universitas Negeri Semarang, 2024)
Spiritual leadership is considered a crucial factor in shaping a positive organizational culture, while a toxic workplace can have negative impacts on employee well-being and performance. This study aims to investigate the influence of spiritual leadership and a toxic workplace on employee performance with the mediation of organizational climate in the Health Office of South Bengkulu. The research utilized purposive sampling with 112 respondents, consisting of medical and staff personnel in the Health Office of South Bengkulu, employing SEM-PLS as the data analysis method. The findings of this study indicate that spiritual leadership, a toxic workplace, and organizational climate have a positive and significant impact on employee performance. Additionally, organizational climate can mediate the relationship between spiritual leadership, a toxic workplace, and employee performance. The practical implications of these findings can assist organizations, particularly the Health Office of South Bengkulu, in developing more effective management strategies to enhance employee well-being and performance.